Integration of Intended Learning Outcomes (ILO) and Course Learning Outcomes (CLO) Real Analysis: An Evaluative Study in the Framework of Outcome-Based Education - Nurnugroho, Burhanudin Arif; Arfinanti, Nurul (Universitas Ahmad Dahlan, 2026)
Background. Outcome-Based Education (OBE) requires strong alignment between Intended Learning Outcomes (ILOs) and Course Learning Outcomes (CLOs) to ensure that graduate competencies are systematically achieved. This study evaluates the extent to which ILO–CLO integration is realised in the Real Analysis course of the Mathematics Education Study Programme. Methods. Using a descriptive evaluative approach, data were obtained through analysis of Semester Learning Plans (SLPs), assessment instruments, student learning outcomes, and interviews with course lecturers. Using assessment data, curriculum documents, and cognitive-level analysis, the study finds that ILO achievement is generally high, with most indicators exceeding 70%. Results. CLO performance shows a varied pattern: students demonstrate strong mastery in Sub-CLO 01 and Sub-CLO 04, particularly in topics with clear procedural structure, such as real number construction and basic calculus. However, achievement in Sub-CLO 03, which covers limits and continuity, remains moderate, indicating difficulties in higher-order reasoning aligned with the expected C5 cognitive level. These results reveal a gap between intended evaluative competencies and the predominantly procedural nature of current assessments. Conclusion. The study recommends integrating more authentic, conceptual, and reasoning-based evaluation methods—such as project or portfolio assessments—to better support deep learning and reflective mathematical thinking.